Senegal: The Resilient Weakness of Casamançais Separatists - (:unkn) unknown (My University, 2007)
The Mouvement des Forces Démocratiques de Casamance, which has been fighting since 1982 for the independence of the region of Casamance, southern Senegal, draws an interesting contrast to the other guerrilla groups of recent African history. First, it is separatist, an oddity in a continent where, dspite predictions to the contrary, separatism have remained rare. Second, while it soon emerged that it could not seriously endanger Dakar's control over most of Casamance and while its internal divisions weakened its capacities, the MFDC has struggled over a long period of time against the state of Senegal, a state that, despite its difficulties in the 1980s and 1990s, was nowhere near the deliquescent or shadowy states of Liberia or Sierra Leone. Third, the MFDC has endured despite a war economy in rags, dependent on a little cannabis and a variety of labor-intensive forest products such as charcoal and cashew nuts. Fourth, it has largely refrained from employing the violent methods which have been so noted in recent African wars, from child soldiers to mass rapes or amputations. Fifth, since the signing of the first ceasefire in 1991, it has been engaged with the Senegalese authorities in a process of negotiation and accomodation so bizarre that, to take but an example, in September 2005, President Wade of Senegal dispatched the head of the Gendarmerie in Casamance to “reassert his trust” in Father Augustin Diamacoune, the leader of the MFDC. None of these features are in themselves unique, but their combination seems to be: a movement both fragile and resilient, waging a war on weak resources against a powerful adversary, a movement which has largely escaped degeneration into ultra-violence, the little-known MFDC provides a fascinating and somewhat counterintuitive case study which may help us refine our interpretation of how armed conflicts develop in Africa and elsewhere.
Keywords: African Research